Distinguishing Benign and Malignant Vertebral Fractures Using CT and MRI - Schwaiger, Benedikt J.; Gersing, Alexandra S.; Baum, Thomas; Krestan, Christian R.; Kirschke, Jan S. (Seminars in Musculoskeletal Radiology, 2016)
The differential diagnosis between benign and malignant vertebral fractures is a common challenge in clinical practice, especially because osteoporotic fractures become more frequent within the aging population and many malignant diseases spread to the bone first, impacting bone integrity. This article reviews the morphological features and computed tomography (CT) and magnetic resonance imaging (MRI) imaging findings that help differentiate between benign and malignant fractures. Newer techniques such as MR-based diffusion-weighted imaging, dynamic contrast-enhanced MR, and chemical-shift imaging as well as hybrid techniques such as positron emission tomography-CT are also discussed briefly.
Keywords: spine; fracture; imaging; osteoporosis; cancer